How society treats smoking - Connolly Gregory N (BMC, 2012)
Abstract Bans on smoking in bars and other public places can make an important contribution to public health. However, for these bans to be effective, they require broad public support. Qualitative studies of the attitudes and perceptions of bar owners and patrons can help public health professionals identify the steps needed to promote public support for smoking bans. Such studies can also generate narratives and quotes that can help public health professionals translate findings on perceptions and attitudes into effective public education campaigns and related policy changes.